JILBAB DAN BATASAN AURAT; TANGGAPAN TERHADAP HUSAEN MUHAMMAD - Rauf, Rusmin Abdul (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
This article aims to critically read Husaen Muhammad’s view of the limits of women’s ‘awrah. According to Husaen Muhammad, the limit of women’s ‘awrah is not something that is agreed upon by all scholars or ijma’. There are many differences of opinion in it. The boundary must refer to the term "what is commonly seen". The thing that is usually seen is certainly different in every culture, so that the boundaries of women’s ‘awrah are certainly different according to each culture. This view, of course, is different from the explanations of the scholars who usually state that the entire body of a woman is ‘awrah except for the face and hands. This article finds that the limitation of women’s ‘awrah is the consensus of the ulama, so it is something that has been qath’i. Therefore, Husaen Muhammad’s view needs to be read critically.